Contrast-enhanced ultrasound pattern of hepatocellular carcinoma in noncirrhotic liver - Results from the prospective multicentre DEGUM CEUS HCC study - Schellhaas, Barbara; Jesper, Daniel; Strobel, Deike (European Journal of Gastroenterology & Hepatology, 2023)
Objectives Contrast-enhanced ultrasound (CEUS) has a high diagnostic accuracy for the noninvasive diagnosis of hepatocellular carcinoma (HCC) in cirrhosis. However, as HCC in noncirrhosis becomes an emerging clinical concern, our study aimed to assess the diagnostic value of CEUS and the CEUS algorithms CEUS LI-RADS and ESCULAP in noncirrhotic liver in a prospective multicentre real-life setting. Methods High-risk patients for HCC with focal liver lesions upon B-mode ultrasound were recruited prospectively in a multicentre real-life approach to undergo standardized CEUS. Diagnostic accuracies of CEUS and the CEUS algorithms were assessed for the sub-collective of noncirrhotic patients. Histology, MRI and CT served as the reference standard. Results In total 47/517 patients were noncirrhotic. The reference standard of the lesions showed 30 HCCs (63.8%), four intrahepatic cholangiocellular carcinomas (iCCAs), two other malignancies and 11 benign lesions. HCCs in noncirrhosis showed a tendency towards larger tumor size and better differentiation. A typical CEUS pattern of arterial phase hyperenhancement and late-onset (>60 s), mild washout occurred in 22/30 HCCs (73.3%). Very late onset of washout > 4-6 min was not seen in noncirrhotic liver. The CEUS algorithm ESCULAP showed a perfect sensitivity (100 vs. 68% with CEUS LI-RADS), whereas CEUS LI-RADS had a superior specificity (83 vs. 53%). The positive predictive value was high with both algorithms. Conclusion The CEUS patterns of HCCs in noncirrhotic liver resembled those in cirrhosis. Our findings suggest that although designed for the application in cirrhosis only, the diagnostic accuracies of the CEUS algorithms in noncirrhotic liver seem comparable to the findings in cirrhosis.
CRIS-Team Scopus Importer:2023-02-10
Keywords: CEUS algorithm; cirrhosis; contrast-enhanced ultrasound; Contrast-Enhanced UltraSound Liver Reporting and Imaging Data System; DEGUM CEUS HCC Study; Erlanger Synopsis for Contrast-enhanced Ultrasound for Liver lesion Assessment in Patients at risk; hepatocellular carcinoma; liver; noninvasive diagnosis; prospective multicentre real-life study